KONTRIBUSI IRWAN ABDULLAH DALAM PENGEMBANGAN KEILMUAN ISLAM DI BIDANG MODERNISASI EKONOMI - Yani, Muhammad Turhan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2009)
From Invan Abdullah’s research, we can a very interesting phenomenon, namely, that Muslim traders in Jatinom (a small town in Klaten, Central Java) can replace the position of Chinese traders and be successful traders until now. To know about their success, Irwan Abdullah conducted a research by studying three interrelated factors: (l) the role of religion in supporting trading activities; (2) trading as a part of broader economic system and as an important factor; and (3) the change of socialreligious factor and social-economic factor in Jatinom Muslim trader society that really cannot be separated from the local political context. According to him, the political structure at the time when economy develops and its changes determine much the development of trading activities. The contributions of this research to Islamic science are: (1) giving the explanation of religion role in supporting human life activities, in this context, trading activities, both concerning with obvious economic behavior of the Muslim traders and the community's response to economic activities; (2) explaining that the role of religion in the process of thinking reformation can lead human behavior, that is, the traders’ economic behavior, and can also influence the way people accept economic activities and trading as a part of their lives.